AHL AL HADITS DAN AHL AL RA’YI - Diah Sugiarti, Lilis; Muhammad Yusup, Rangga; Anwar, Syahrul (LPPM Universitas Bina Bangsa, 2025)
This research discusses two main schools of thought in the development of Islamic law, namely Ahl al-Hadith and Ahl al-Ra'yi, which were prominent in the early period of the formation of fiqh. Ahl al-Hadith emphasizes the importance of the authority of Islamic texts, especially the Koran and hadith, in establishing law. They tend to reject the use of independent reasoning or ijtihad outside these sources, for fear of deviating from original teachings. In contrast, Ahl al-Ra'yi opens up more space for logical reasoning and analogies (qiyas) in addressing legal issues that are not explicitly regulated in the text. They consider ijtihad important to respond to new situations that arise in society. This difference reflects the tension between literal and rational approaches in Islamic law, which later influenced the formation of schools of fiqh such as the Hanafi School and the Hanbali School. This article aims to outline the methodological differences between these two schools and their impact on the development of classical and contemporary Islamic law.